2006
DOI: 10.1016/j.exer.2005.09.021
|View full text |Cite
|
Sign up to set email alerts
|

Stromal haze, myofibroblasts, and surface irregularity after PRK

Abstract: The aim of this study was to investigate the relationship between the level of stromal surface irregularity after photorefractive keratectomy (PRK) and myofibroblast generation along with the development of corneal haze.Variable levels of stromal surface irregularity were generated in rabbit corneas by positioning a fine mesh screen in the path of excimer laser during ablation for a variable percentage of the terminal pulses of the treatment for myopia that does not otherwise generate significant opacity. Nine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
209
0
10

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 245 publications
(227 citation statements)
references
References 21 publications
8
209
0
10
Order By: Relevance
“…According to these studies, the disruption of the epithelial basement membrane correlates with the differentiation of myofibroblasts due to the release of transforming growth factor beta-1 [31] followed by myofibroblast-expressed SMA. Although the damage caused to the basement membrane in the incision for ICRS implantation is small, we also found ∝−SMA-positive cells around the segment, although there were fewer than after other procedures, such as phototherapeutic keratectomy [32] and PRK [39]. These cells were α-SMA-positive from one month to three months, which correlated with the appearance of haze around the segment, as reported in other studies [23,40,41].…”
Section: Discussionsupporting
confidence: 69%
“…According to these studies, the disruption of the epithelial basement membrane correlates with the differentiation of myofibroblasts due to the release of transforming growth factor beta-1 [31] followed by myofibroblast-expressed SMA. Although the damage caused to the basement membrane in the incision for ICRS implantation is small, we also found ∝−SMA-positive cells around the segment, although there were fewer than after other procedures, such as phototherapeutic keratectomy [32] and PRK [39]. These cells were α-SMA-positive from one month to three months, which correlated with the appearance of haze around the segment, as reported in other studies [23,40,41].…”
Section: Discussionsupporting
confidence: 69%
“…Hence, although these matrices may regulate tumor cell growth, any observed effect is not necessarily comparable to that produced by a fibroblast-rich stroma. Moreover, a plethora of reports have suggested that the thinning or degradation of basement membranes at early stages of tumor development is a frequent event (Akashi et al, 2005;Capo-Chichi et al, 2002;Netto et al, 2006). This early basement membrane degradation facilitates a more direct contact between the neoplastic epithelial cells and the adjacent mesenchymal compartments.…”
Section: Introductionmentioning
confidence: 99%
“…During corneal wound healing, most patients experience transient changes in corneal transparency (9) . Injury to the epithelium and removal of the central epithelial basement membrane, which also occur in PRK, initiate a complex sequence of events mediated by Intraocular straylight before and after low myopic photorefractive keratectomy with and without mitomycin C epithelial-stromal interactions (10,11) . Corneal fibroblast and myofibroblast generation, in addition to changes in the quality and quantity of extracellular matrix, are the main alterations contributing to stromal opacity following PRK surgery (9,12) .…”
Section: Introductionmentioning
confidence: 99%